Philosophy of science : a very short introduction - Okasha, Samir ([Oxford] : Oxford University Press, 2016)
This 'Very Short Introduction' provides a concise overview of the main themes of contemporary philosophy of science. After a short history, the author goes on to investigate the nature of scientific reasoning, scientific explanation and more.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 20, 2016).
Keywords: Science -- Philosophy